Lean Manufacturing and Industry 4.0: Unveiling Trends, Applications, and Global Impacts in Manufacturing Through Comprehensive Literature Review - Aida Azizah Nor Azian; Rusalbiah Che Mamat; Dzullijah Ibrahim; Falah Abu (Penerbit Universiti Kebangsaan Malaysia, 2025)
Despite extensive research on the association between life satisfaction and city-level economic, socio-demographic, and management variables, few studies have explored the spatial and socio-economic aspects of neighbourhood environments, particularly in developing countries. This study aims to fill this gap by investigating the determinants of life satisfaction, with a focus on the impact of various neighbourhood environment aspects on residential satisfaction and overall subjective well-being in Jeddah, Saudi Arabia. A comprehensive residential satisfaction survey was conducted in 2020, involving 405 randomly selected households from 14 neighbourhoods. Using an ordinal logistic regression model, the study analyzed the perceived significance of physical and socio-demographic attributes in residential areas. The fi ndings reveal 24 key determinants of both overall life satisfaction and residential satisfaction, classified into four primary dimensions: demographic attributes, housing characteristics, the physical environment of the neighbourhood, and the social environment. Additionally, the study established a significant association and mutual relationship between life satisfaction and residential satisfaction. This research contributes to the theoretical debate and empirical research on life satisfaction by highlighting the crucial role of the residential environment in predicting overall subjective well-being. It underscores the importance of integrating life satisfaction into policies aimed at enhancing the residential environment. The implications of this study suggest that urban planners and policymakers need to prioritize improving neighbourhood conditions to enhance the quality of life for residents, particularly in developing urban contexts. By addressing these determinants, cities can foster environments that promote higher life satisfaction and well-being among their inhabitants. Keywords: Overall Equipment Eff ectiveness (OEE); Manufacturing Execution System (MES); Internet of Things (IoT), Lean Manufacturing 4.0; Smart Factory